2020
DOI: 10.1093/cid/ciaa663
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomic Characterization of Coronavirus Disease 2019 Identified a Host Transcriptional Classifier Associated With Immune Signaling

Abstract: BACKGROUND The recent identification of a novel coronavirus, also known as SARS-CoV-2, has caused a global outbreak of respiratory illnesses. The rapidly developing pandemic has posed great challenges to diagnosis of this novel infection. However, little is known about the metatranscriptomic characteristics of patients with Coronavirus Disease 2019 (COVID-19). METHODS We analyzed metatranscriptomics in 187 patients (62 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
91
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 52 publications
(70 reference statements)
12
91
3
3
Order By: Relevance
“…Importantly, several of the taxa reported to change between intubated and nonintubated patients were reported to be linked to diagnosis in previous COVID-19 microbiome studies [15][16][17] . In our study, no taxa were differentially abundant between COVID-19 positive and negative patients after controlling for patient intubation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Importantly, several of the taxa reported to change between intubated and nonintubated patients were reported to be linked to diagnosis in previous COVID-19 microbiome studies [15][16][17] . In our study, no taxa were differentially abundant between COVID-19 positive and negative patients after controlling for patient intubation.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies exploring other pulmonary disorders have shown that lung microbiota may exacerbate their symptoms and contribute to their severity 13 , potentially through direct crosstalk with the immune system and/or due to bacteremia and secondary infections 14 . Few studies of the respiratory microbiome in COVID-19 have revealed elevated levels of opportunistic pathogenic bacteria [15][16][17] . However, reports on bacterial diversity are contradictory.…”
Section: Covid-19 a Novel Coronavirus Disease Classified As A Pandemmentioning
confidence: 99%
“…In cardiomyocytes, there is an up-regulation of genes responsible for IFN-γ suppression, also suggesting an effect IFN-γ in the cardiac function, in a sepsis-like pattern [ 28 ]. Furthermore, the relationship of IFN-γ disruption is not only associated with COVID-19 and the immune system, but there is a relationship of microbiome modification, altering the cell transcriptome with gene overexpression, which can be associated with the cytokine storm [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in another study with 62 COVID-19 patients was found a reduced alpha diversity in microbes. 75 The metatranscriptional analysis revealed that there were 36 differentially genes associated with immune pathways and cytokine signaling related to the diagnosis and severity of COVID-19, such as interferon-gamma signaling. 74 Despite reporting interesting patterns, the studies mentioned above are not without limitations.…”
Section: The Effects Of Covid-19 On the Gut Microbiomementioning
confidence: 99%